On the residual properties of damaged FRC - Zerbino, Raúl (2017)
A discussion on the residual behaviour of Fibre Reinforced Concrete (FRC) is performed based on two selected cases of concrete degradation: the exposure at High Temperatures and the development of Alkali Silica Reactions. In addition, and taking in mind that the failure mechanism in FRC is strongly related with the fibre pull-out strength, the bond strength in damaged matrices was shown concluding that the residual bond strength is less affected than the matrix strength. As the damage increases, the compressive strength and the modulus of elasticity decrease, being the modulus of elasticity the most affected. There were no significant changes produced by the incorporation of fibres on the residual behaviour when compared with previous experience on plain damage concrete. Regarding the tensile behaviour although the first peak decreases as the damage increases, even for a severely damage FRC the residual stresses remain almost unaffected.